Text Mining Techniques for Analyzing the Subjectification of Knowledge Workers in Organizational Contexts - Charles Liam (Indus Journal of Social Sciences, 2023)
This research explores the subjectification of knowledge workers within organizational contexts using advanced text mining techniques. Subjectification, the process by which individuals construct their identities and subjectivities, is of paramount importance in understanding the dynamics of contemporary knowledge work. Drawing on textual data from interviews, surveys, and organizational documents, this study employs natural language processing (NLP) and text mining methodologies to uncover patterns, themes, and insights related to the subjectification experiences of knowledge workers. Our findings shed light on the interplay between power, discourse, organizational structures, and the construction of professional identities among knowledge workers in the modern workplace.